Monitoring and evaluation of physical abilities, as the basic elements of learning management students, aiming at the development of personality in the physical training. - Volkov V.L (Kharkov National Pedagogical University, 2011)
It is considered the problem of managing of pedagogical influence on the identity of university students in the process of physical training. The study involved 237 boys 17-19 years, who are trained in basic medical group for physical education. It is defined the content control over the physical fitness of students of pedagogical specialists. It is developed a differentiated evaluation of the physical abilities of youth with age-appropriate development of the organism.